2009
DOI: 10.1007/s10649-009-9200-6
|View full text |Cite
|
Sign up to set email alerts
|

Mathématiques de la vie quotidienne au Burkina Faso: une analyse de la pratique sociale de comptage et de vente de mangues

Abstract: Mathematics teaching in Burkina Faso is faced with major challenges (high illiteracy rates, students' difficulties, and high failure rates in mathematics, which is a central topic in the curriculum). As evidenced in many of these studies, mathematics is reputed to be tough, inaccessible, and far from what students live daily. Students here look as though they are living in two seemingly distant worlds, school and everyday life. In order to better understand these difficulties and to contribute in the long run … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
0
1
Order By: Relevance
“…Regarding the pulp, the fiber content obtained was 9.88 which is higher than that of Haq (2006) who showed that jackfruit pulps in Bangladesh had fiber contents between 1% and 1.5%. This result is also higher than that (1.87%–2.77%) found by Traore (2020) on pineapple pulp in Burkina Faso. These high fiber contents make jackfruit harvested in Bertoua, Cameroon an essential food in the prevention of constipation, colon cancer, diabetes, and cardiovascular diseases (Bemmo et al, 2023).…”
Section: Discussioncontrasting
confidence: 64%
“…Regarding the pulp, the fiber content obtained was 9.88 which is higher than that of Haq (2006) who showed that jackfruit pulps in Bangladesh had fiber contents between 1% and 1.5%. This result is also higher than that (1.87%–2.77%) found by Traore (2020) on pineapple pulp in Burkina Faso. These high fiber contents make jackfruit harvested in Bertoua, Cameroon an essential food in the prevention of constipation, colon cancer, diabetes, and cardiovascular diseases (Bemmo et al, 2023).…”
Section: Discussioncontrasting
confidence: 64%
“…El estudio de los conocimientos matemáticos con poblaciones específicas, en contextos laborales y de la vida cotidiana, con adultos no alfabetizados, niños trabajadores y poblaciones marginalizadas, en general, ha sido ampliamente documentado por la investigación en educación matemática (Carraher et al , 1995;Lave, , 2011Soto, 2001;De Agüero, 2006;Fuenlabrada y Delprato, 2005;Ávila, 2009;Kalman y Solares 2018;Solares 2011Padilla y Solares-Rojas, 2013;Rogoff, 1990;Traoré y Bednarz, 2009).…”
Section: Antecedentes Y Marco De Referenciaunclassified